2012
DOI: 10.1002/tox.21779
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal di‐n‐butyl phthalate exposure alters reproductive functions at adulthood in male rats

Abstract: This study was aimed to investigate the reproductive health in adult male rats exposed to di-n-butyl phthalate (DBP) during embryonic development. Pregnant rats were injected with DBP and F1 male rats were weaned and on postnatal day 100, used for mating with normal cycling females to assess reproductive performance. After completion of cohabitation period, rats were analyzed for other reproductive end points. Transplacental exposure to DBP significantly decreased fertility in adult male rats. Prenatal exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 61 publications
2
36
0
Order By: Relevance
“…These abnormalities are consistent with inhibiting fetal testosterone production (Scott et al, 2009). Moreover, decreases in testicular or serum testosterone levels in juvenile male rats (≤ postnatal days 35) (Shultz et al, 2001;Mylchreest et al, 2002;Fisher et al, 2003;Fisher, 2004) and in adult male rats Wakui et al, 2013Wakui et al, , 2014Giribabu et al, 2014) were described after in utero DBP exposure. Leydig cells (LC) are the cells that synthesize testosterone.…”
Section: Introductionsupporting
confidence: 51%
“…These abnormalities are consistent with inhibiting fetal testosterone production (Scott et al, 2009). Moreover, decreases in testicular or serum testosterone levels in juvenile male rats (≤ postnatal days 35) (Shultz et al, 2001;Mylchreest et al, 2002;Fisher et al, 2003;Fisher, 2004) and in adult male rats Wakui et al, 2013Wakui et al, , 2014Giribabu et al, 2014) were described after in utero DBP exposure. Leydig cells (LC) are the cells that synthesize testosterone.…”
Section: Introductionsupporting
confidence: 51%
“…Reduction of testosterone level is probably due to the reduction of number of Sertoli cells, since the function and survival of Leydig cells in adulthood is dependent on persistent presence of Sertoli cells [22,23]. Furthermore it has been shown that prenatal exposure of male rat to Di-n-Butyl Phthalate (DBP) (anti-androgen, which reduces androgen level) decreases the activity level of testicular steroidogenic enzymes, as well as testosterone level in adults [16]. Another study demonstrated that prenatal exposure of male rat to testosterone propionate, during days 17-19 of gestation, will lead to reduction of plasma testosterone level during adulthood [10].…”
Section: Discussionmentioning
confidence: 99%
“…Sperm solution preparation were carried out according to the method described by Giribau, N et al [16] with some modification. In brief, animals were anesthetized by intraperitoneal injection (i.p) of pentobarbital sodium (P3761, 5mg, Sigma, USA) dissolved in normal saline 0.9% (60 mg/kg body weight), immediately after anesthesia; the right epididymis was removed, weighed and then transferred to petri dish containing 2 ml of normal saline, caudal portion of epididymis isolated, split with needle then 20 µl semen removed from caudal portion of epididymis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This “phthalate syndrome” is characterized by malformations in the male reproductive organs, retention of nipples, and reduced anogenital distance (AGD) [11, 12]. Moreover, gestational exposures to different phthalates have been shown to reduce fertility in male rodents by decreasing steroidogenic capacity, sperm quality and quantity, and sexual behaviors [1316]. However, the effects of prenatal phthalate exposure on female reproduction in the offspring are less extensively studied.…”
Section: Introductionmentioning
confidence: 99%